Assessment of prognostic factors in pediatric adrenocortical tumors: a systematic review and evaluation of a modified S-GRAS score. Issue 6 (26th October 2022) - Riedmeier, Maria; Decarolis, Boris; Haubitz, Imme; Reibetanz, Joachim; Wiegering, Armin; Härtel, Christoph; Schlegel, Paul-Gerhardt; Fassnacht, Martin; Wiegering, Verena
Abstract : Objective: Pediatric adrenocortical carcinoma (pACC) is rare and prognostic stratification remains challenging. We summarized the clinical prognostic factors of pACC and determined the prognostic value of the pediatric scoring system (pS-GRAS) in adaption to the recommendation (S-GRAS) of the European Network for the Study of Adrenal Tumors for the classification of adult ACC. Design: Analysis of pACC patients of 33 available retrospective studies in the literature. Methods: We searched the PubMed and Embase databases for manuscripts regarding pACC. The pS-GRAS score was calculated as a sum of tumor stage (1 = 0; 2–3 = 1; 4 = 2 points), grade (Ki67 index/rate of mitosis 0–9%/low = 0; 10–19%/intermediate = 1; ≥20%/high = 2 points), resection status (R0 = 0; RX = 1; R1 = 2; R2 = 3 points), age (<4 years = 0; ≥4 years = 1 point), hormone-related symptoms (androgen production = 0; glucocorticoid/mixed/no hormone production = 1 point) generating 10 scores and 4 groups (1: 0–2, 2: 3–4, 3: 5, 4: 6–9). The primary endpoint was overall survival (OS). Results: We included 733 patients. The median age was 2.5 years and >85% of pACC showed hormone activity (mixed 50%, androgen 29%, glucocorticoid 21%). Androgen production was associated with a superior OS. Increasing age correlated with higher rates of inactive or only glucocorticoid-producing tumors, advanced tumor stage, and case fatality. Especially infants < 4 years showed more often low-risk constellations with an increased OS for all tumor stages. The pS-GRAS score correlated with clinical outcome; median OS was 133 months (95% CI: 36–283) in group 1 ( n = 49), 110 months (95% CI: 2.9–314) in group 2 ( n = 57), 49 months (95% CI: 5.8–278) in group 3 ( n = 18), and 16 months (95% CI: 2.4–267) in group 4; ( n = 11) P < 0.05). Conclusion: The pS-GRAS score seems to have a high predictive value in the pACC patients, may serve as a helpful tool for risk stratification in future studies, and should be evaluated prospectively in an international context.